Enhancing Financial Performance of Islamic Banks in Indonesia: The Mediating Effect of Green Banking Disclosure on Corporate Governance Practices - Nabilah Febriyane Prasetyo Widodo; Dian Imanina Burhany; Sumiyati Sumiyati; Neneng Dahtiah (Jurusan Akuntansi Politeknik Negeri Bandung, 2023)
Increasing environmental pollution due to business activities was addressed by issuing POJK Number 51/POJK.03/2017. In the banking sector, green banking practices and disclosures are a form of responsibility towards environmental sustainability. However, disclosure of green banking in Islamic commercial banks is still relatively low, as is financial performance, which is not optimal. Thus, it is necessary to examine the factors that influence the disclosure of green banking and fraud to improve financial performance. This study uses governance factors, namely board size, an independent board of commissioners, and gender diversity, to influence financial performance mediated by green banking disclosures. The research sample is 12 Islamic banks in Indonesia for the 2017–2022 period. The results show that green banking disclosure is only influenced by the size of the board of commissioners and independent commissioners, while financial performance is influenced by the size of the board of commissioners, independent commissioners, and gender diversity. Furthermore, disclosure of green banking can mediate the correlation of the board of commissioners and independent commissioners on financial performance.